Epilepsy in the elderly: comparing clinical characteristics with younger patients. (3rd February 2014) - Stefan, H.; May, T. W.; Pfäfflin, M.; Brandt, C.; Füratsch, N.; Schmitz, B.; Wandschneider, B.; Kretz, R.; Runge, U.; Geithner, J.; Karakizlis, C.; Rosenow, F.; et al.
<x xml:space="preserve">Abstract</x> The prevalence and incidence of epilepsies in elderly is high. Due to demographic development, the portion of elderly patients with epilepsy will continue to rise over the next decades. In this study, we aimed to investigate seizure semiology, etiology, comorbidity, and therapy in elderly patients dependent on onset of epilepsy and in comparison with younger patients. In a prospective multicentre study, 202 epilepsy patients were included in a consecutive manner and subdivided into three groups (group A1: >65 years, onset of epilepsy after the age of 65 years; group A2: >65 years with early onset epilepsy, seizure onset before the age of 50 years; and group B: <50 years with epilepsy). Clinical data with respect to epilepsy, seizures, comorbidity, etiology, and anti‐epileptic drug (AED) therapy were assessed using a questionnaire developed especially for these patient groups and filled out by the physicians. The clinical profile with regard to etiology, postictal conditions, and comorbidities clearly depends on the age of the patients and age of onset of epilepsy. Patients with an epilepsy onset after 65 years need lower doses of AEDs, gain better seizure control and have more concomitant diseases than younger patients or elderly epilepsy patients with early‐onset epilepsy.